Regulation of Cholesterol Metabolism in the Dog: II. EFFECTS OF COMPLETE BILE DIVERSION AND OF CHOLESTEROL FEEDING ON POOL SIZES OF TISSUE CHOLESTEROL MEASURED AT AUTOPSY - Pertsemlidis, Demetrius (1973)
In six adult pedigreed dogs the effects of high-cholesterol diets or bile diversion on the sizes of body cholesterol pools were studied at autopsy. Total body cholesterol was determined by measuring the cholesterol content of discrete organs and of the eviscerated carcass: neither cholesterol feeding nor bile diversion had altered total body cholesterol or the cholesterol content of individual organs and tissues. These results validated the conclusion based on sterol balance data obtained during life, that high-cholesterol feeding did not lead to substantial expansion of tissue cholesterol pools. The total amount of exchangeable cholesterol in the animals with an intact enterohepatic circulation, when estimated from isotopic data, was essentially the same as that measured chemically: this indicated that there was little or no nonexchangeable cholesterol in these dogs, except in skin and nervous tissue, regardless of the cholesterol content of the diet. This correspondence of estimates was not obtained in the bile-diverted dogs: we propose that the defect in the isotopic estimates was due to the accelerated rate of cholesterol synthesis in these animals. Gross and microscopic morphology of all organs and tissues was examined. Abnormal findings were limited to the biliary tract and the urinary collecting system of the two bile-diverted dogs: multiple bilirubinate gallstones were found, and mild pyelitis and ureteritis were present on the side of the bilio-renal shunt, but the urinary bladder was normal. Histologic evidence of moderate degree of cholangitis was found in one of the two bile-shunted dogs, but in neither dog was there evidence of impedance of bile flow.